LO72: Spotting potential opportunities for teachable moments. (May 2020) - Alrimawi, H.; BCh, MB; Sample, S.; Chan, T.
Abstract : Introduction: With the transition of Emergency Medicine into competency based medical education (CBME), entrustable professional activities (EPAs) are used to evaluate residents on performed clinical duties. This study aimed to determine if implementing a case-based orientation, designed to increase recognition of available EPAs, into CBME orientation would help residents increase the number of EPAs completed. Methods: We designed an intervention consisting of clinical cases that were reviewed by national EPA experts who identified which EPAs could be assessed from each case. A case-based session was incorporated into the 2019 CBME orientation for The McMaster Emergency Medicine Program. Postgraduate Year (PGY)1 residents read the cases and discussed which EPAs could be obtained with PGY2/faculty facilitators. The number of EPAs completed in the first two blocks of PGY1 was determined from local program data and Student's t-test was used to compare averages between cohorts. Results: We analyzed data from 22 trainees (7 in 2017, 8 in 2018, and 7 in 2019). In the first two blocks of PGY1, the intervention cohort (2019) had a significantly higher average number of EPAs completed per trainee (47.4 [SD 11.8]) than the historical cohort (25.3 [SD 6.7]) (p < 0.001) (Cohen's d = 2.3). No significant difference existed in the number EPAs obtained between the 2017/2018 cohorts, with averages of 24.3 [SD 6.8] and 26.1 [SD 7.0] per trainee respectively (p = 0.6). Conclusion: Implementation of a case-based orientation led by CBME-experienced facilitators nearly doubled the EPA acquisition rate of our PGY1s. The consistent EPA acquisition by the 2017/2018 cohorts suggest that the post-intervention increase was not solely due to developed familiarity with the CBME curriculum.